A STUDI LITERATUR: PENINGKATAN NUMERASI PESERTA DIDIK DENGAN PENERAPAN PEMBELAJARAN DIFERENSIASI TINGKAT SMA/MA/SMK: Asesmen Nasional, Kurikulum Merdeka, Matematika, Model Pembelajaran, dan Pendekatan Pembelajaran - Robiah Adawiah, Eka Elia; In In Supianti (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2024)
Mathematics is one of the basic sciences that has an important role in the development of science and technology. In the world of education, thinking skills need to be developed in the learning process, especially to solve mathematical problems (Hanany and Sumaji, 2020). Numeracy ability is a person's intellectual ability that involves systematic and logical thinking processes in carrying out arithmetic operations (Gunur, 2018). Investigation of students' numeracy abilities is an important thing to do. By analyzing the learning process and the results of students' numeracy abilities, it can be seen what students' numeracy abilities are. Therefore, it is necessary to use a learning model that can improve the ability to solve numeracy problems, one of which is the application of differentiated learning that can accommodate students' needs. The research method used is a qualitative literature study, which analyzes findings from various previous studies. The research results show that differentiated learning not only increases students' learning activities and outcomes, but also increases students' learning motivation. Statistical analysis of these studies also increases the effectiveness of differentiated learning in students' numeracy abilities